Assessing cross cultural urban park emotional wellbeing impact in Shanghai and London - Zijuan Zhao; Qingying He; Yaqiong Zhang; Sidi liu; Ying Yang (Scientific Reports)
Abstract Urban parks serve as restorative environments that can alleviate stress and improve mood. However, quantifying the emotional benefits of parks and uncovering geographic differences across regions presents challenges. This study aims to compare the cross-cultural impact of urban parks on visitors’ positive emotions between Shanghai and London. We collected text data from Weibo and Twitter, applying natural language processing techniques to quantify emotion scores. A LightGBM regression model was used to explore the nonlinear relationships between park environments and positive emotions, while a Multiscale Geographically Weighted Regression (MGWR) model was constructed to reveal spatial heterogeneity and its underlying causes. The results indicate that all environmental variables have nonlinear effects on visitors’ positive emotions, with cross-cultural differences reflected in emotional responses: (1) Cross-cultural factors play an important role in influencing positive emotions of visitors in different regional urban parks, mainly reflected in different emotional well-being. (2) In Shanghai, higher economic vitality and greater walkability enhanced visitors’ positive emotions in urban parks. (3) In London, high accessibility does not promote visitors’ positive emotions, showing a contrast to the effect observed in Shanghai. However, higher education density and lower parking lot density contributed to positive emotions for park visitors in London. (4) Visitors in Shanghai are more likely to experience positive emotions in medium-sized parks, while in London, visitors tend to feel more pleasant in small parks. The findings of this study indicate that the park environment plays a significant role in fostering positive emotions in visitors. Additionally, future research could explore the impact of socio-cultural factors on emotional responses, expanding beyond the focus on the park’s physical attributes.